Microstructure-based fatigue life model of metallic alloys with bilinear Coffin-Manson behavior. (February 2018) - Cruzado, A.; Lucarini, S.; LLorca, J.; Segurado, J.
Highlights: The origin of bi-linear Coffin-Manson is identified as the redistribution of plastic microfields. A microscopic FIP allows predicting fatigue life in the whole strain range. All the features of the cyclic behavior such as cyclic softening are accounted for life prediction. The model predicts the influence of the strain ratio in life at low strain amplitudes. The scatter in life is accounted for showing a strong scatter reduction for large strain amplitudes. Abstract: A microstructure-based model is presented to predict the fatigue life of polycrystalline metallic alloys which present a bilinear Coffin-Manson relationship. The model is based in the determination of the maximum value of a fatigue indicator parameter obtained from the plastic energy dissipated by cycle in the microstructure. The fatigue indicator parameter was obtained by means of the computational homogenization of a representative volume element of the microstructure using a crystal-plasticity finite element model. The microstructure-based model was applied to predict the low cyclic fatigue behavior of IN718 alloy at 400 °C which exhibits a bilinear Coffin-Manson relationship under the assumption that this behavior is triggered by a transition from highly localized plasticity at low cyclic strain ranges to more homogeneous deformation at high cyclic strain ranges. The model predictions were in very good agreement with the experimental results for a wide range of cyclic strain ranges and two strain ratios ( R ε = 0 and −1) and corroborated the initial hypothesis. Moreover, they provided a micromechanical explanation for the influence of the strain ratio on the fatigue life at low cyclic strain ranges.